Conjugated polyelectrolyte with pendant carboxylate groups: Synthesis, photophysics, and pH responses in the presence of surfactants - Zhang, Tao; Fan, Hongliang; Zhou, Jianguang; Jin, Qinhan (Journal of polymer science. Part A, Polymer chemistry, 2009)
This article reports the synthesis, optical properties, and pH responses of a water-soluble poly(phenylene ethynylene) with pendant carboxylate groups. This conjugated polyelectrolyte, PPE-OBS, was prepared via a facile synthetic route, using 1,4-di(ethyl 4-oxy-butyrate)-2,5-diiodo-benzene as polymeric monomer and followed by the alkali induced saponification. PPE-OBS absorbs strongly in the blue region and emits a moderately intense fluorescence. However, it subjects to unstable emission in neutral aqueous media, which is believed to arise because the polymer tends to become more hydrophobic via protonation and to form much heavier aggregates (clusters). Subsequent studies on the interaction and stabilization of PPE-OBS with various surfactants indicate that its fluorescence stability can be largely improved in the presence of a small amount of surfactant. More interestingly, even at low pH, the surfactant-stabilized polyelectrolyte with its pendant groups being ---COOH rather than ---COO⁻ remains water-soluble and emits efficiently, which is expected of great significance for the covalent linkage to bio-molecules. In addition, the sensitive pH response in emission spectrum of PPE-OBS/surfactant complex over a relatively wide range suggests surely a potential access to the fluorescent sensing of pH variation.